Thymic Function Failure Is Associated With Human Immunodeficiency Virus Disease Progression. (4th February 2017) - Ferrando-Martinez, Sara; De Pablo-Bernal, Rebeca S.; De Luna-Romero, Marta; De Ory, Santiago J.; Genebat, Miguel; Pacheco, Yolanda M.; Parras, Francisco J.; Montero, Marta; Blanco, Jose Ramón; Gutierrez, Felix; Santos, Jesus; Vidal, Francisco; et al.
Summary: Thymic function, determined by signal-joint/DβJβ T-cell rearrangement excision circle ratio, correlates with HIV disease progression. This work establishes the relevance of the thymus in HIV disease progression, helping to clarify the mechanisms underlying the rationale of early combination antiretroviral therapy onset. Abstract: Background: Thymic function has been mainly analyzed with surrogate peripheral markers affected by peripheral T-cell expansion, making it difficult to assess the role of thymic failure in human immunodeficiency virus (HIV) disease progression. The assay of signal-joint/DβJβ T-cell rearrangement excision circles (sj/β-TREC ratio) overcomes this limitation but has only been assayed in small cohorts. Thus, the aim of this study was to determine the role of thymic function, measured by the sj/β-TREC ratio, on CD4 T-cell maintenance in prospective HIV cohorts that include patients with a wide age range and different immunological phenotypes. Methods: Seven hundred seventy-four patients including typical progressors, long-term nonprogressors (LTNPs), and vertically HIV-infected subjects were analyzed. Thymic function was quantified in peripheral blood samples using the sj/β-TREC ratio. Associations between thymic function and CD4 T-cell dynamics and combination antiretroviral therapy (cART) onset were analyzed using linear, logistic, and Cox proportional hazard models. Results: Thymic function failure (sj/β-TREC ratio <10) was independently associated with HIV progression. In agreement, patients with distinctive high CD4 T-cell levels and low progression rates (vertically HIV-infected patients and LTNPs, including HIV controllers) had significantly higher thymic function levels whereas patients with thymic function failure had lower CD4 T-cell levels, lower nadir, and faster CD4 T-cell decay. Conclusions: This work establishes the relevance of thymic function, measured by sj/β-TREC ratio, in HIV disease progression by analyzing a large number of patients in 3 cohorts with different HIV disease progression phenotypes. These results support and help to understand the mechanisms underlying the rationale of early cART onset.